Internet usage, innovation and human development nexus in Africa: The case of ECOWAS - Jeremiah O. Ejemeyovwi; Evans Osabuohien; Olawale D. Johnson; Ebenezer I. K. Bowale (Journal of Economic Structures, 2019)
Internet usage and the sporadic rise in the level of innovations have been major drivers of human progress in the last decades. These leaps in human intelligence have affected almost every area of human endeavour including education, health, finance, commerce, political engagement, and so on. With the United Nations' Sustainable Development Goals (SDGs), the Economic Community of West African States (ECOWAS) has adopted some strategies in order to ensure that ECOWAS member countries are not left behind. Thus, this study examines the influence of internet usage and innovation on human development in 15 ECOWAS countries. Using the fixed and random effects panel data techniques, the study finds that Internet usage, innovation and their interaction have significant and positive relationship with human development. Furthermore, the study unbundles the ECOWAS countries and finds that countries like Cape Verde had positive significant coefficient for the three cases examined, the results for some ECOWAS members were not significant, while few had significant negative results, which did not have influence on the overall result. Recommendations on how to increase innovation for human development in ECOWAS countries are highlighted in the study.
Keywords: 330; Internet usage; Human development; ECOWAS countries; Innovation; SDGs; Technical Knowledge; Knowledge economy